Analysis of Factors Affecting The Level of Survival of Fishermen In Jangka District, Bireuen Regency - Adhiana Adhiana; Suryadi Suryadi; Riani Riani (Return : Study of Management, Economic and Bussines, 2023)
Indonesia's fisheries and marine resources have a very important role, but abundant marine resources are not matched by the better life of coastal communities. Limited access and loss of living assets are serious problems faced by poor people in coastal areas, thus affecting their livelihoods. This research was conducted in Masa District, Bireuen Regency from July to November 2022. Purposive determination of the location of the study considering that the sub-district is one of the areas with the highest number of fishing households in Bireuen Regency. The population of capture fishermen was 9,432 people, and the number of samples obtained was 120 fishermen. The sampling method uses accidental sampling techniques. The data in this study will be analyzed with the SEM (Structural Equation Modeling) Model. The purpose of this study is to analyze the factors that affect the level of sustainability of fishermen's lives in Masa District, Bireuen Regency, and analyze the relationship between vulnerability, life assets, strategies and the sustainability of fishermen's lives. Based on the results of the study, it was found that the factors that affect the sustainability of fishermen's lives are life strategies and ownership of living assets. The fourth relationship is that increased vulnerability positively affects fishermen's living assets, increasing the availability of living assets positively affects fishermen's life strategies. Increasing ownership of living assets positively affects the sustainability of fishermen's lives and increasing life strategies positively affects the sustainability of fishermen's lives.